2004
DOI: 10.1038/sj.gene.6364046
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the interleukin-20 gene: relationships to plaque-type psoriasis

Abstract: We analyzed the frequency of single-nucleotide polymorphisms (SNPs) at positions À1053 (rs 2981572), 1380 (rs 2981573), 1462 (rs 2232360), and 3978 (rs 1518108) of the human interleukin-20 (IL-20) gene by tetraprimer ARMS-PCR method. A significant association between patients with psoriasis and the G allele at position À1053 (Po0.05) was established. The pairwise linkage disequilibrium (LD) matrix showed that the nearly complete LD was present within the polymorphisms at positions À1053, 1380, and 1462 of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 19 publications
3
40
0
1
Order By: Relevance
“…The novelty of the present study lies in the extension of the risk haplotype already described in IL- 20 21 It is reasonable to expect that described haplotypes really determine the differences in IL-19 and -20 expression levels. Supportive to this functional hypothesis is that we described two haplotypes with opposite effects-one protective and another one for susceptibility.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The novelty of the present study lies in the extension of the risk haplotype already described in IL- 20 21 It is reasonable to expect that described haplotypes really determine the differences in IL-19 and -20 expression levels. Supportive to this functional hypothesis is that we described two haplotypes with opposite effects-one protective and another one for susceptibility.…”
Section: Discussionmentioning
confidence: 83%
“…A significant association between patients with psoriasis and the G allele at position À1053 and GAA haplotype was established. 20 In the present study, we attempted to clarify the role of IL-19 gene in predicting risk for psoriasis using study population identical to the one used for IL- 20 …”
Section: Introductionmentioning
confidence: 99%
“…In the individual evaluation of IL-20 SNPs, we demonstrated that rs1518108 heterozygous genotype T/C had a protective effect against psoriasis (P ¼ 0.03). 31 As the IL-24 gene follows the IL-20 gene in the human genome, the LD analysis was performed between the IL-20 rs1518108 and the polymorphisms of IL-24 gene. The pairwise LD matrix indicated the significant LD (|D 0 | between 0.61 and 0.79) ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…11,[15][16][17] For each SNP, a set of four primers was designed using the online program available at http: //cedar.genetics.soton.ac.uk/public_html/primer1.html. Each PCR reaction was carried out in a total volume of 10 ml, containing 100 ng of template DNA, 20 pmol of each inner primer, 2 pmol of each outer primer, 0.2 mM deoxyribonucleotide triphosphate, 1 Â reaction buffer (75 mM Tris-HCl, pH 8.8, 20 mM (NH 4 ) 2 SO 4 , 0.01% Tween 20, 0.1 mg ml À1 Tartrazine, 1% Sucrose (Naxo, Tartu, Estonia), 0.5 U Smart-Taq DNA polymerase (Naxo).…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Evidence was obtained that the IL19 gene cluster represents a susceptibility region shared by plaque-type psoriasis and palmoplantar pustulosis (PPP), offering a possible explanation at the genetic level for the frequent co-existence of PPP and plaque-type psoriasis. [15][16][17][18] The biological activities of the IL-19 subfamily cytokines are mediated through binding to two distinct cell-surface receptors, the IL-20 receptor type I (IL-20-RI) and type II (IL-20-RII). Both receptors are heterodimers and share the IL-20RB protein as common subunit.…”
Section: Introductionmentioning
confidence: 99%